(untitled) (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Grief, a personalized response to the loss of a significant other, often leads to seeking medical consultation. Objective: To evaluate and compare the attitudes to be used by family medicine doctors (m-FM) and the expectations of bereaved individuals. Methods: An exploratory, cross-sectional observational study was conducted on a sample of m-GP, chosen conveniently, and on individuals who have been in mourning for less than a year, applying a specifically designed clinical case and response to similar medical attitudes and expectations in closed multiple-choice and open-ended options. The application process took place after consultation and was also conducted remotely, following an invitation from the m-MGF, by the inclusion criteria. Readability analysis of the text and descriptive and inferential statistics of the data were performed. Results: In a sample of 21 m-MGF, 13 (46.4%) women and n=12 (57.1%) specialists, and from 20 people, n=15 (75.0%) were women. Significant differences were found in the responses of m-MGF and people (p<0.001), with empathetic counseling being the most chosen option by m-MGF, 69.6%, and people, 27.5%. For 91.7% of the specialists, only empathetic counseling was selected, with specialty interns responding with more options (p=0.014). People significantly chose more associations of therapeutic attitudes, 31.7% (n=13), than GPs, 2.4% (n=1, p<0.001). Discussion: The differences found in this unprecedented study, simultaneously academic and practice-oriented, regarding medical attitudes and the expectations of people in the face of a bereavement case, suggest the need for a more comprehensive approach by doctors in managing people in mourning, such as the use of empathy, person-centered medicine, and social prescription. Conclusion: In this sample, despite the same attitudes and expectations, differences were observed between m-MGF and people. Doctors predominantly opted for empathetic counseling (69.6%), while people chose other simultaneous approaches.